The Anti-virus Properties of Nano-Chinese Medicine Microcapsule Treated Fabrics (Journal of Fiber Bioengineering and Informatics, 2008)
The extracted components of Chinese medicine were prepared by following differentmethods and were used to make microcapsules of the medicine. The two agent samples of the nano-Chinese medicine microcapsule agent and the Chinese medicine Microcapsule agent and two treatedfabrics, was used to determine the anti-virus properties of influenza virus and Herpes simplex virus byfluorescent quantification polymerase chain reaction (FQ-PCR). The testing conditions included theagent concentrations of original liquid, 1/10, 1/100, 1/1000 and 1/10000, and virus contents of 5.00 &#215 107, 5.00 &#215 105, 5.00 &#215 103, 5.00 &#215 102copies/ml. The results indicated that all of the two agent samplesof the nano-Chinese medicine microcapsule agent, the Chinese medicine microcapsule agent and thetreated fabrics have good anti-virus characteristics. The nano-Chinese medicine microcapsule agent wasmore effective than the Chinese medicine microcapsule agent. The original style and good properties ofthe woollen fabrics were basically kept.